2014
DOI: 10.1371/journal.pone.0113448
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of DWV Associated to Flower Pollen: Experimental Evidence of a Horizontal Transmission Route

Abstract: Deformed wing virus (DWV) is a honeybee pathogen whose presence is generally associated with infestation of the colony by the mite Varroa destructor, leading to the onset of infections responsible for the collapse of the bee colony. DWV contaminates bee products such as royal jelly, bee-bread and honey stored within the infected hive. Outside the hive, DWV has been found in pollen loads collected directly from infected as well as uninfected forager bees. It has been shown that the introduction of virus-contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 28 publications
(47 reference statements)
2
91
1
Order By: Relevance
“…It implies that horizontal transmission of LSV can occur via infected bees, via the vectoring mite or via contaminated pollen. Although we do not provide causal evidence of transmission, cross-species transmission of honey bee viruses and subsequent infection has previously been experimentally demonstrated (Furst et al, 2014;Mazzei et al, 2014;Singh et al, 2010).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It implies that horizontal transmission of LSV can occur via infected bees, via the vectoring mite or via contaminated pollen. Although we do not provide causal evidence of transmission, cross-species transmission of honey bee viruses and subsequent infection has previously been experimentally demonstrated (Furst et al, 2014;Mazzei et al, 2014;Singh et al, 2010).…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, the demonstration of virus replication in the solitary bee O. cornuta suggests that LSV is a multi-host virus, akin to other honey bee viruses such as DWV and IAPV. This solitary bee is also susceptible to DWV infection (Mazzei et al, 2014), but replication of these viruses is demonstrated in several pollinators (Levitt et al, 2013;Li et al, 2011;Zhang et al, 2012). Even clinical symptoms of an overt DWV infection, such as crippled wings, have been observed in bumble bees (Genersch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…and viable DWV particles have been found in pollen (Mazzei et al, 2014;McArt et al, 2014;Singh, 2011). Both honey bees and C. smaragdula were found foraging on the same common garden herbs, crops, and ornamentals -such as Scaevola sericea (Naupaka) and Heliotropium foertherianum -on both Oahu and Maui (pers.…”
Section: Floral Resources Have Been Identified As a Potential Contactmentioning
confidence: 99%
“…host varroa mites that can vector DWV, it is assumed that bumble bees and other wild bee species acquire DWV though robbing of DWVinfected colonies of Western honey bees for honey or, more likely, by collection and ingestion of DWV with pollen or nectar from flowers that are also visited by DWV-infected Western honey bee workers [27 , 39,40]. Given this assumption, we highlight two issues that confound the interpretation of data on DWV prevalence in wild bee species in terms of impact on hosts.…”
Section: Dwv Prevalence and Impactmentioning
confidence: 99%